Air-Sea Interactions in the Formation of Thunderstorms over Marmara Region: Physical Processes and Modelling - Yavuz, Veli (Graduate School, 2022)
Thunderstorm and sea-effect snow (SES) are meteorological events that adversely affect both daily life and the transportation sector, and occur as a result of air-sea interaction. Thunderstorm, is a meteorological phenomenon that usually contains strong winds and causes strong precipitation (e.g., rain, hail) accompanied by lightning. Intense atmospheric instability, high humidity, vertical triggering mechanisms, and wind shears are essential components for thunderstorm formation. Thunderstorms caused by cumulonimbus clouds occur both with precipitation and without precipitation. On the other hand, they occur not only with rain, but also with snow and hail. This phenomenon, known as a severe weather event, occurs as a result of convectional movements. For this reason, the increasing differences between the upper atmospheric level air parcel temperature and the sea or lake surface temperatures play an intensifying role in thunderstorm activities. SES occurs as a result of atmospheric instability, which occurs as a result of dry and cold air masses gaining heat and moisture fluxes as they pass over warmer water bodies. As a result of the instability of very cold and dry air parcels of arctic or polar origin during their passage over the Black Sea located in the north of our country, the Marmara Region and the Black Sea Region are exposed to SES in the winter months. Although SES cause heavy snowfalls in regions where they are effective as severe weather events, they do not need synoptic-scale systems to occur. SES that occur in a region where synoptic-scale systems are currently dominant are called as snowfall with increased sea effect. This type of snowfall causes more intense snow on the regions where the SES bands pass. In our country, there are studies on both severe weather events mentioned above. There are both case studies and climatological analyses in the literature regarding the thunderstorm event. However, climatological analyses and short-term forecast models are limited in terms of their effects on the Marmara Region and especially on the aviation sector. On the other hand, there are a very limited number of studies in the literature regarding the SES events for our country. There is no climatological comprehensive analysis or a prediction mechanism established for certain sectors for this event, where only a few assessments and case studies are included in the international literature. Both a knowledge and a scientific base are needed for this severe weather event, which is very effective in the northern parts of our country during the winter months and directly affects both daily life and transportation activities. In this context, in this thesis, a total of nine articles, two on thunderstorm events and seven articles on SES, were published in six different internationally refereed journals. In the first article, a short-term forecast of the thunderstorm that occurred at Istanbul Atatürk International Airport on February 2, 2015 was made. It has been determined that the thunderstorm and its severity can be predicted in the range of 42-57 minutes in advance by analysing radar images, Lightning Detection Tracking System (LDTS), sea surface temperature information, and surface/upper level atmospheric information. It has been revealed that this result is important for the decision makers working in the meteorology office. In the second article, various 15-year long-term statistics of thunderstorm events were investigated at 11 airports in the Marmara Region. Atmospheric conditions in which thunderstorm events occur and the effects of air-sea interaction were examined. Intraday, monthly, and annual distributions were analszed. No trend was determined on an annual basis, and the most observations were made in September on a monthly basis. In the daytime thunderstorm distribution, the most observations occurred between 1100-1900 hours. 72% of thunderstorms occurred with rain and 22% without any precipitation. One of the most important results of the study is that the Convective Available Potential Energy (CAPE) is zero in approximately 50% of the events. In the third article, the morphological classification of SES bands was made for the Danube Sea Area (western Black Sea) in the Black Sea. Between 2009 and 2018, SES bands were observed over the region in a total of 83 days, and these bands caused snowfall within the borders of the Marmara Region in 75 days. Various satellite and radar images obtained from the Turkish State Meteorological Service (TSMS) were used for the detection of SES bands. In total, five different types of SES bands have been defined for the region. The most common type of band among all events was Type-2 SES band with 85%. The most important reason for this is that this band type consists of parallel bands in the longitudinal direction. The north-south movements of polar and arctic air masses along the long fetch distance of the western Black Sea have created suitable atmospheric conditions for the Type-2 band. On average, the lowest sea surface temperatures (SESs) occurred in the northernmost part of the Danube Sea Area. This region is the region where SES bands mostly begin to form and are of weak intensity. The intensity of the bands increased due to the increasing SST towards the south. In the fourth article, the analysis of vortex (Type-5) SES bands that occurred in the western Black Sea on January 30-31, 2012 was carried out. The vortex band, which was detected with various images of two different satellites (Terra and MSG satellites), continued its effect on the region for approximately 24 hours. The structure of the vortex was analysed by analysing the surface level meteorological data obtained from 12 airports, 16 meteorological stations, and 5 radiosonde stations belonging to the countries surrounding the western Black Sea and various charts of the upper atmospheric levels. The 24 cm of snow depth was measured at the İnebolu meteorology station, where the SES bands connected to the vortex were effective, and a total of 102 flights were canceled across the countries surrounding the western Black Sea. In addition to these, many traffic accidents have also occurred due to heavy and sudden snowfalls. The surface and upper level atmospheric conditions that create the vortex were found as follows: presence of a strong/deep inversion layer between the surface and 700 hPa, the wind direction change being limited to a maximum of 50° in the same vertical range, the temperature difference reaches 25.8 °C in between the sea surface and 850 hPa at the point where the vortex core is located. In addition, in the analyses made with the synoptic charts, it was determined that the vortex was formed during the two-day period and there was a low pressure centre in the region where the core is located. In the fifth article, the statistical characteristics of SES events for the western Black Sea were analysed for the years 2009-2018. The main purpose of the study is to determine the meso- and synoptic-scale structures of SES events for the region in general and to create knowledge for nowcasting and forecasting applications to be made later. A total of 95 events were detected using satellite and radar images. These events were determined according to four different scale categories. As a result, 36 events (38%) are determined as Black Sea (BS) Events, 24 (25%) as Synoptic-scale (SYNOP) Events, 23 (24%) as Over Sea Convergence (OSC) Events, and 12 (13%) as Transition (TRANS) Events. While the average duration of SES events in four different categories was 15.9 hours, the longest time was 59 hours in the SYNOP Events. Except for the OSC Events, the prevailing wind direction under the inversion layer was northerly in all three categories. Inversion layer was detected in most of the BS Events and SYNOP Events, and the sea surface and upper level temperature difference was 4 °C to 6 °C higher on average compared to the other two categories. The highest number of events occurred in January with 51, and the lowest in March with 2. In the sixth article, the effect of short-wave troughs on the formation and development of SES bands in the western Black Sea was investigated. Between 2010 and 2018, a total of 48 short-wave troughs and long waves were detected in the presence of SES bands throughout the region. The most important role of long waves has been realized as a result of determining the direction of short-wave troughs. Afterwards, short-wave troughs and long waves were classified based on their direction of motion. Five different types of short-wave troughs and five different types of long waves were determined, and their monthly and annual statistics, and their durations were revealed. In addition, the temperature differences between sea surface and upper atmospheric levels were analysed for each type, and inversion conditions were examined. The average duration of short-wave troughs was found to be 27.8 hours, and the longest time was observed in LWT type with 60 hours. In 77% and 79% of all events, respectively, short-wave troughs and long waves were found to have the same direction of motion as the current SES bands. In the seventh article, thundersnows occurring in the Marmara Region within a 22-year period were investigated. For these events, the formation mechanisms, suitable surface, sea, and upper level atmospheric conditions were investigated. Based on the reports of 11 airports in the region, a total of 19 incidents were identified. In 17 of these events, the SES mechanism was found to be effective. After statistical temporal analysis, the predictability of these events was investigated with atmospheric stability indices. Accordingly, the most successful stability indices were Total Total Index and TQ Index. In the eighth article, a comparison of SES and non-SES for two international airports in Istanbul is made. A SES event prediction algorithm was developed for both airports using 10 years of atmospheric data. At the same time, suitable atmospheric conditions were determined according to the snow depths. Finally, in the ninth article, historical extreme winters in Istanbul were investigated. The events that took place within the scope of the 17-century period are shown, and based on the events that took place in the last few centuries, heavy snowfall and harsh winter forecasts are made for the period up to 2050 and 2100.
Marmara Bölgesi'nde Orajların Oluşumunda Hava-Deniz Etkileşimlerinin Etkisi: Fiziksel Süreçler ve Modelleme
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: thunderstorm; oraj; snow; kar; Marmara Region; Marmara Bölgesi; atmospheric conditions; atmosferik koşullar